Approximal Fluoride Concentration Using Different Fluoridated Products Alone or in Combination - Särner, B.; Birkhed, D.; Lingström, P. (Caries research, 2008)
The aim of the present investigation was to measure the approximal fluoride (F) concentration after using different F-containing products, either alone or in combination. Ten subjects participated on a total of 17 occasions, which were randomized, distributed and divided into two trials (called trial I and trial II). The F concentration was studied after treatment with toothpicks, dental flosses, an interdental brush dipped in 0.2 or 0.32% F gels, brushing with toothpaste containing 0.32% F and a mouthrinse with 0.2% NaF solution. The results of trial I revealed that the rinsing solution resulted in the highest approximal F values, followed by toothpicks and brushing. When brushing was combined with either flossing or toothpick, the sequence order of the two methods had less influence. However, when combined with rinsing it appeared to be better to use the floss or the toothpicks first, prior to the mouthrinse. In trial II, treatment with the gels alone, and in combination with brushing, resulted in higher approximal F concentrations compared with brushing alone. The data indicate that the order of usage when combining products may be of importance when it comes to obtaining high F levels at the approximal sites and that an interdental brush with F gel after toothbrushing may be a suitable method, called ‘Inter Dental Brush Gel Method’, to produce elevated F concentrations at approximal sites.